Haploidentical CD7 CAR T-cells induced remission in a patient with TP53 mutated relapsed and refractory early T-cell precursor lymphoblastic leukemia/lymphoma - Hai-ping Dai; Wei Cui; Qing-ya Cui; Wen-juan Zhu; Hui-min Meng; Min-qing Zhu; Xia-ming Zhu; Lin Yang; De-pei Wu; Xiao-wen Tang (BMC, 2022)
Abstract Patients with relapsed/refractory early T-cell precursor lymphoblastic leukemia/lymphoma (ETP-ALL/LBL) respond poorly to traditional therapy and have dismal prognosis. CD7 is a promising therapeutic targets for chimeric antigen receptor modified T cell therapy (CART) due to its widely expression in almost all T-cell malignancies. Here we present the anti-CD7 CART therapy in a 11-year-old male with TP53 mutated relapsed/refractory ETP-ALL/LBL. The patient suffered second relapse after haploidentical hematopoietic stem cell transplantation, showing resistance to 4 lines salvage therapies including venetoclax. Nanobody derived CD7-CART cells were manufactured by co-transducing CAR-T cells with a CD7 protein expression blocker. 70.5% of blasts (CD7 expression: 92.6%) and extensive extramedullary disease (mediastinal mass, enlarged lymph nodes and spleen) were observed prior to CD7-CART-cell therapy. A total of 5 × 106/kg donor-derived CD7-CART-cells were infused. Hematological and extramedullary remission were both achieved, with persistence of CD7-CART-cells be detected until the last followup at 96th days after the infusion. Reversible adverse effects including grade 3 cytokine release syndrome and macrophage activation syndrome were observed. This case demonstrated that CD7-CART was a potent and safe salvage therapy in relapsed/refractory ETP-ALL/LBL patient with high tumor burden. Trial registration: ClinicalTrials. gov, NCT04785833 , Registered on March 8, 2021, prospectively registered.